Influence of a nearby substrate on the reorganization energy of hole exchange between dye molecules. Issue 11 (21st March 2015) - Manke, Fabian; Frost, Jarvist M.; Vaissier, Valérie; Nelson, Jenny; Barnes, Piers R. F.
<x xml:space="preserve">Abstract</x> The outer-sphere reorganisation energy for hole transfer between dye molecules in polar solvents is reduced by around 20% by dielectric substrates.